Concept development in Nursing and Midwifery: An overview of methodological approaches. Issue 1 (19th October 2018) - Beecher, Claire; Devane, Declan; White, Mark; Greene, Richard; Dowling, Maura
Abstract: Background: Over the past four decades, there has been a growing focus on the resolution of conceptual problems through the process of concept development. As the focus on this area has grown, so too has the number of debates in the literature on methodological aspects of concept development. Aim: To provide an overview of the essential methodological considerations of concept development. Design: Discussion paper. An overview is presented of the methodological considerations of commonly used concept development strategies and methods within nursing and midwifery. Data Sources: Literature dating from the inception of concept development in nursing and midwifery. Implications for Nursing and Midwifery: The robust development of concepts is a vital component in advancing the knowledge base of nursing and midwifery theory and practice. However, the complexity of the concept development literature may serve to exacerbate the challenges of developing a given concept, in particular for the novice researcher. Conclusion: The methodological considerations discussed provides guidance in determining the most appropriate strategy and method of concept development. SUMMARY STATEMENT: What is already known about this topic? Over the past four decades there has been a growing focus on the resolution of conceptual problems in the nursing and midwifery domain through the process of concept development; The growing focus on the area of concept development has led to a proliferation of debates in relation to almost all aspects of the methodology of concept development. The complexity of these debates ensures that for the novice researcher the translation and effective utilization of concept development literature is often problematic. What this paper adds? The clarification of the intended use of various concept development strategies and explication of the fundamental methodological principles of four commonly used concept development methods will guide nurse and midwife researchers in their choice of concept development methodology. The implications of this paper: The overview presented provides nurse and midwife researchers with a basis on which to build their knowledge of concept development.